Smoking Among Adolescents and Associated Factors in Rural Areas - Hanida Hani Mohd Mokhtar; Nurul Farhana Abdul Ghani; Siti Nur Illiani Jaafar; Aini Ahmad; Fitri Arofiati (Fakultas Ilmu Keperawatan Universitas Indonesia, 2023)
Smoking among adolescents is the major health-related issues in Malaysia. However, information concerning recent smoking rates and how they correlate among adolescents in rural areas is still limited. This study aimed to determine the percentage of adolescent smokers among high school students, examine their level of nicotine dependence, and study the association between sociodemographic data and smoking status. A cross-sectional study was conducted at one of the high schools located in the rural area of Bandar Tun Abdul Razak, Pahang, Malaysia. A convenience sampling method was used to select the participants, as only Form 2 students were available during the data collection. In total, 113 respondents were recruited for the study. The data, which were collected using self-administered questionnaires were analyzed using chi-square analysis and Fisher’s exact test analysis. The results showed that the prevalence of adolescent smokers among high school students was quite high (25.7%). Among the adolescent smokers, 65.5% had low nicotine dependence, and 34.5% had moderate nicotine dependence. Moreover, 21.4% of them admitted that they had tried other substances or drugs in addition to cigarettes. Peer pressure was the major factor in smoking (69.0%), followed by curiosity (27.6%), and then smoking family members’ influence, stress or tension, and others (3.4% each). The only significant association (p < 0.001) was between gender and smoking status. These findings showed that the proportion of smokers among adolescents is increasing over the years; thus, effective strategies, such as peer advocacy of smoking cessation, may be needed among this population. Keywords: adolescent, peer influence, rural areas, smoking, students Abstrak Merokok di Kalangn Remaja dan Faktor-faktor yang Memengaruhinya di Daerah Pedesaan. Merokok di kalangan remaja adalah masalah kesehatan utama di Malaysia. Namun, informasi mengenai tingkat perokok saat ini dan korelasinya di kalangan remaja di daerah pedesaan masih terbatas. Penelitian ini bertujuan untuk mengetahui persentase remaja perokok di kalangan siswa sekolah menengah atas (SMA), mengetahui tingkat ketergantungan nikotin, dan mempelajari hubungan antara data sosiodemografi dengan status merokok. Sebuah studi cross-sectional dilakukan di salah satu SMA yang terletak di daerah pedesaan Bandar Tun Abdul Razak, Pahang, Malaysia. Metode convenience sampling digunakan untuk memilih peserta, hanya siswa Form 2 yang bersedia selama pengumpulan data. Sebanyak 113 responden direkrut untuk penelitian ini. Data yang dikumpulkan menggunakan kuesioner yang dikelola secara mandiri, dan dianalisis menggunakan analisis chi-square dan analisis Fisher’s exact test. Hasil penelitian menunjukkan bahwa prevalensi perokok remaja pada siswa SMA cukup tinggi (25,7%). Di antara remaja perokok, 65,5% memiliki ketergantungan nikotin tingkat rendah, dan 34,5% memiliki ketergantungan nikotin tingkat sedang. Terlebih, 21,4% di antaranya mengaku pernah mencoba zat atau obat lain selain rokok. Tekanan dari orang terdekat (teman) merupakan faktor utama dalam merokok (69,0%), diikuti oleh rasa ingin tahu (27,6%), dan pengaruh anggota keluarga yang merokok, stres atau ketegangan, dan lain-lain (masing-masing 3,4%). Satu-satunya hubungan yang signifikan (p < 0,001) adalah antara jenis kelamin dan status merokok. Temuan ini menunjukkan bahwa proporsi perokok di kalangan remaja meningkat dari tahun ke tahun; oleh karena itu, strategi yang efektif, seperti advokasi sejawat untuk berhenti merokok, diperlukan di kalangan populasi ini. Kata Kunci: daerah pedesaan, merokok, pengaruh teman sebaya, remaja, siswa